Model Keputusan Politik Rezim Teknokrat di Indonesia (Studi pada Periode Presiden B.J Habibie) - Agung Setiawan; Eti Yusnita; Hatta Azzuhri (Jurnal Prodi Ilmu Politik, 2022)
The title of this research is the Political Decision Model of the Technocrat Regime in Indonesia (Study During the Period of President B.J Habibie). The formulation of the problem in this research is how is the decision model of the technocrat regime in Indonesia (Presidential B.J Habibie Period Study) and what are the factors behind the technocratic regime's political decision model in Indonesia (Presidential B.J Habibie Period Study) literature as a reference. President B.J Habibie was sworn in on May 21, 1998, the first policy of President BJ. Habibie immediately announced and inaugurated a new cabinet called the Development Reform Cabinet on 22 May 1998. There were 36 ministers, consisting of 20 ministers for department heads, 12 ministers for state and 4 coordinating ministers. The Cabinet reflects all elements of the nation's strength, including the United Development Party, the Indonesian Democratic Party, the Working Group, ABRI, regional elements, scholars, and non-governmental organizations. Embracing all the political and social potential is the early democracy to demand reform. The basis of B.J Habibie's decision model comes from his proximity to Suharto as President of the Republic of Indonesia, young B.J Habibie Nationalism, B.J Habibie as an Expert in Science and Technology, introduction of B.J Habibie with Islamic figures, political situation and conditions of the New Order in 1990-1998. Keywords: Decision Model, Technocrat, B.J Habibie